Advances in Digital Manufacturing Systems Technologies, Business Models, and Adoption - Amit, R. K.; Pawar, Kulwant S.; Sundarraj, R. P.; Ratchev, Svetan (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book contains contemporary discussions on technology, business models, and the adoption of digital manufacturing systems. The book's initial chapters cover technological details underpinning the digital manufacturing systems, for example, cyber-physical systems and digital twins. Next, the book discusses how organizations modify their business models using concepts such as servitization and platforms to leverage digital manufacturing. The latter chapters focus on how a country's unique economic and infrastructural context influences digital manufacturing adoption in terms of technology and business models and frameworks to evaluate readiness for digital manufacturing. With perspectives from different continents, the book appeals to academic researchers and industry alike.
Introduction -- Chapter 1. History and Future of Manufacturing -- Chapter 2. Developments of Technological Systems -- Chapter 3. Digital Manufacturing -- Chapter 4. Business Models for Additive Manufacturing: A Consulting Services Perspective -- Chapter 5. Servitization in the digital era -- Chapter 6. Manufacturer's Decisions for Sharing Products: Challenges, Opportunities and Optimal Strategic Plan -- Chapter 7. A Study on Mathematical Models for Transforming the Job-Shop Layout into Flow-Shop Layout -- Chapter 8. Cross-Country Comparative Analysis of Digital Manufacturing Systems -- Chapter 9. Towards a Standard Framework for Organizational Readiness for Technology Adoption -- Chapter 10. Case studies of implementation approach to assessing and evaluating digitalization readiness -- Chapter 11. Smart Factories and Indian MSME.
Keywords: Business information services; Electronic commerce; Production management; Industrial Management; IT in Business; E-Business.; Business Information Systems; Operations Management; Industrial Management